Two-dimensional μXAFS analysis for accumulated uranium in kidneys of rats exposed to uranyl acetate. (October 2020) - Homma-Takeda, Shino; Uehara, Akihiro; Yoshida, Takanori; Numako, Chiya; Sekizawa, Oki; Nitta, Kiyofumi; Sato, Nobuaki
Abstract: Kidneys are critical targets of uranium exposure, meaning that effective analytical methods for characterizing uranium accumulated in kidneys are required in toxicological studies of uranium. In this work, synchrotron radiation micro-X-ray fluorescence (SR-μXRF) imaging and two-dimensional　μXAFS measurements were combined to analyze renal section specimens. By histochemical staining of the serial sections, the distribution of uranium chemical condition within the uranium-concentrated areas of the proximal tubules, which are toxic target sites of uranium, were obtained with 1 µm × 1 µm spatial resolution. Highlights: The combination of SR-μXRF and μXAFS for rat renal section specimens. Two-dimensional μXAFS for uranium concentrated areas in renal tubules in kidney. The distribution of biotransformation of uranium in a micro-region.